Comparative Analysis of Value Increase and Prediction Asset Growth Between Bitcoin, Gold, and World Stock Index - Ary Yusdianto; Kartika Hendra Ts; Supawi Paawenang (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Technological developments have transformed nearly every aspect of society, including investment methods. The types of investments that frequently attract investors are digital assets in the form of cryptocurrencies, stock indices, and gold. Comparative research on these three types of investments is still limited, particularly regarding Bitcoin. Therefore, this study analyzes the asset values ​​of these three types of investments and their predicted growth as considerations in determining promising investments. This quantitative descriptive study analyzes variables using the CAGR (Compound Annual Growth Rate) and AAGR (Average Annual Growth Rate) parameters for Bitcoin, gold, and stock indices in the United States, China, Germany, and Indonesia for the 2020–2024 period. The data is then used to predict asset growth over the next five years (2025–2029). The results show that the three types of assets studied for the 2020–2024 period exhibited growth in value with distinct profile characteristics. Bitcoin, the most volatile asset, offers the potential for significant long-term returns. Meanwhile, the assets with the best potential for growth in the 2025–2029 period, starting with the highest ranking, are Bitcoin, the S&P 500 (United States), and Gold. The predicted values ​​based on AAGR and CAGR for Bitcoin assets in 2029 are Rp75,664,861,688 and Rp7,575,357,132, respectively. Consideration of macroeconomic factors, along with strengthening government regulations and market education, is necessary for successful economic growth. Future research on digital assets such as Ethereum or stablecoins, and analysis of the impact of crypto adoption by countries as national reserves using other parameters, are needed to strengthen references and considerations for future investment options, taking technological advancements into account.